PENGARUH KUALITAS JASA TERHADAP KEPUASAN PASIEN YANG DIMEDIASI OLEH CITRA RUMAH SAKIT (STUDI PADA PASIEN RAWAT INAP DI RUMAH SAKIT TIARA SENTOSA KENDARI) - La Ode Man Sabdar; Hasanuddin Bua; Hayat Yusuf; Dedy Takdir Syaifuddin; Sinarwaty Sinarwaty; Abd. Razak Yusuf (Jurnal Manajemen, Bisnis dan Organisasi (JUMBO), 2020)
This study aims to: 1) examine the influence of service quality on hospital image, 2) examine the effect of service quality on patient satisfaction, 3) examine the influence of hospital image on patient satisfaction, 4) examine the effect of service quality on patient satisfaction mediated by hospital image. The type of this  research is explanatory research, then seen from the approach of research strategy or data collection process, this research uses survey method.  The population in this study was all patients treated at Tiara Sentosa Kendari Hospital. For sampling techniques researchers use non random or non probability selection in the form of purposive sampling. A total of 135 samples were obtained using the formula Hair et al (2010). Data is collected by interview methods and questionnaires. The analysis tool used is Partial Least Square (PLS). The results showed that both directly and indirectly, the quality of services has a positive and significant effect on patient satisfaction at Tiara Sentosa Kendari Hospital.